2017
DOI: 10.1177/1467358417715677
|View full text |Cite
|
Sign up to set email alerts
|

Tourists’ perspectives on hard and soft services toward rural tourism destination competitiveness: Community support as a moderator

Abstract: Rural tourism is an integrated part in the services field, and this industry has long been recognized as a valuable tool for economic development in rural destinations. However, the multiplying growth of rural tourism destinations has led to a stiff competition among the industry. Thus, the identification of tourists’ perspective on the hard and soft services components toward the development of rural tourism is a key element in surviving into the rapid tourism competition. The pivotal role of community suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 91 publications
(108 reference statements)
1
39
0
4
Order By: Relevance
“…A balanced attention to resources, the community, and the economy is essential to achieve the sustainability of ecotourism [118]. In this sense, those papers that address social factors (welfare of the local population and community support) and economic factors (hospitality of residents, safety and security, tourism infrastructure, accommodation, availability of diverse activities, value for money in shopping items, the quality of restaurants), become important as a basis for the analysis of competitiveness [119,120] and emerge as an unavoidable future line of research.…”
Section: Cluster 0: Destination Competitivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…A balanced attention to resources, the community, and the economy is essential to achieve the sustainability of ecotourism [118]. In this sense, those papers that address social factors (welfare of the local population and community support) and economic factors (hospitality of residents, safety and security, tourism infrastructure, accommodation, availability of diverse activities, value for money in shopping items, the quality of restaurants), become important as a basis for the analysis of competitiveness [119,120] and emerge as an unavoidable future line of research.…”
Section: Cluster 0: Destination Competitivenessmentioning
confidence: 99%
“…In this sense, the importance of the local population being aware of the value of its social and natural resources, and that tourism can help its economic development is highlighted [127]. Thus, together with economic and environmental perceptions, socio-cultural factors and life satisfaction should be considered key elements to enhance tourism sustainability [119,128].…”
Section: Cluster 2: Socio-cultural Factorsmentioning
confidence: 99%
“…However, Reitsamer et al (2016) have found that tourists' well-being has a significant impact to local people income and also have positively effect of their intention to return, so that, become more attractive effect on the desire to settle a positive word of mouth of the destination. Lo et al (2019) has reported on research study of community support as an integral part of tourism product in supporting tourism destination quality, especially in rural sector . Lo et al (2019) has found that sustainable development of rural tourism destination play an important role for developing rural tourism together with community participation.…”
Section: Introductionmentioning
confidence: 99%
“…Lo et al (2019) has reported on research study of community support as an integral part of tourism product in supporting tourism destination quality, especially in rural sector . Lo et al (2019) has found that sustainable development of rural tourism destination play an important role for developing rural tourism together with community participation. Compared with other research, Lo et al (2019) significantly found that the competitiveness of rural tourism destination's development is depend on community support act as a moderator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation